Antibiotic Residues in Foods of Animal Origin: Review - Mgonja, Frida Richard; Paul, Kaswija John (Journal of Biology and Life Science, 2024)
Antibiotic residue in food is a serious public health issue that demands much attention and has a harmful impact on consumer health. The presence of antibiotic residue in food of animal origin creates challenges in global trade in animals and animal products. Public health implications of antibiotic residue in food include the development and propagation of antimicrobial drug resistance, hypersensitivity reactions, carcinogenicity, mutagenicity, teratogenicity, bone marrow suppression, and disruption of normal intestinal flora. Improper use of antibiotics in animals results in the existence of residues beyond maximum limit levels and is associated with harmful health effects in humans. Supervision of antibiotics is required to ensure the safety of animal products. In this review, the use of antibiotics in food animals, antibiotic residues in foods of animal origin, and the effect of different cooking techniques on antibiotic residue levels are discussed.